EFFECT OF THE NITRIDING PROCESS IN THE WEAR BEHAVIOUR OF DIN 1.2344 HOT WORK STEEL - (:unkn) unknown (My University, 2020)
Gas nitriding is a widely applied thermochemical surface treatment, whichis applied to enhance mechanical properties and wear characteristics ofiron and steels. The impact of the gas nitriding process on the mechanicaland wear resistance characteristic of DIN 1.2344 (X40CrMoV5-1) hot worksteel were investigated in this paper. Nitrided and non-nitrided sampleswere characterized through a different method such as the opticalmicroscope, scanning electron microscopy, energy dispersive spectrometry,X-ray diffraction, atomic force microscope (AFM) and 3D opticalprofilometer. The results of analyses reveal that increases in wearresistance of the nitrided sample due to the formation of surface layers ofnitrides and oxides.

Gaz nitrasyon yöntemi demir ve çeliklerin mekaniksel özelliklerini ve aşınma karakteristiklerini geliştirmek için uygulanan bir termokimyasal yüzey işlemidir. Bu çalışmada DIN 1.2344 (X40CrMoV5-1) sıcak iş takım çeliğine uygulanan gaz nitrasyon işleminin mekanik özelliklerine ve aşınma direncine etkisi araştırılmıştır. Nitrürlenmiş numune ve işlem görmemiş referans numune optik mikroskop, SEM EDX, X ışını difraksiyonu, atomik kuvvet mikroskopu ve 3D optik profilometre yoluyla karakterize edilmiştir. Analiz sonuçları nitrürlenmiş numune yüzeyinde oluşan nitrür alaşımları ve oksidasyon tabakası sayesinde aşınma direnci artış meydana geldiğini göstermiştir.
NİTRASYON İŞLEMİNİN DIN 1.2344 SICAK İŞ TAKIM ÇELİĞİNİN AŞINMA DAVRANIŞLARI ÜZERİNE ETKİLERİ